Pengembangan Komik Digital Ekonomi Interaktif Berbasis Nilai Karakter Untuk Meningkatkan Hasil Belajar Siswa Di MAN 3 - Tuzuhro, Fatimah; Hutasuhut, Saidun; Tambunan, Khairuddin E (Universitas Hamzanwadi, 2024)
The presence of the Independent Curriculum is one of a number of efforts to maximize the quality of education in Indonesia that is in accordance with the urgency of the times through character education, therefore facilities are needed in the form of teaching materials packaged with character values. This research study aims to develop teaching materials assisted by comic media based on character values ​​to help improve learning outcomes. The researcher used the 4D development model, (Define, Design, Develop, Disseminate). The instrument sheets used were (1) material expert validation sheet, (2) media expert validation sheet (3) learning design expert validation sheet, (4) student initial needs sheet. The results of the study showed that interactive digital economic comic teaching materials based on character values ​​obtained results for material experts of 92% with the category